Early Childhood Mathematics: Promoting Good Beginnings. A joint position statement (Edma 0-6: Educación Matemática en la Infancia, 2013)
A joint position statement of the National Association for the Education of Young Children (NAEYC) and the National Council of Teachers of Mathematics (NCTM) on Early Childhood Mathematics. Adopted in 2002. Updated in 2010.
Keywords: Mathematics Education; Early Childhood Education; National Association for the Education of Young Children; National Council of Teachers of Mathematics